2015
DOI: 10.2135/cropsci2013.10.0706
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Application on Yield and Irrigation Water Use Efficiency in Corn under Limited Irrigation

Abstract: Drought, and rising water and pumping costs dictate that continued production of corn (Zea mays L.) will be limited in future years if effective water conservation strategies are not established. This study was conducted to evaluate the effect of irrigation regimes in conjunction with surfactant treatments on field corn grain yield (GY), total dry matter (TDM) production, and irrigation water use efficiencies (IWUE) based on GY and TDM in a distinct Mediterranean climate, at Spadra Ranch in Pomona, CA, for 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
6
12
0
Order By: Relevance
“…The surfactant treatment showed a significant influence on IWUE in all treatments (Figure 7). These results are supported by the previous reports by Chaichi et al (2015) who explained that by application of surfactant in irrigation water, both IWUE and GY (grain yield) of corn increased.…”
Section: Water Use Efficiency (Wue) For Seed Yieldsupporting
confidence: 91%
See 4 more Smart Citations
“…The surfactant treatment showed a significant influence on IWUE in all treatments (Figure 7). These results are supported by the previous reports by Chaichi et al (2015) who explained that by application of surfactant in irrigation water, both IWUE and GY (grain yield) of corn increased.…”
Section: Water Use Efficiency (Wue) For Seed Yieldsupporting
confidence: 91%
“…Thus, the outcome of this research indicated that by increasing the severity of limited irrigation, the amount of irrigation water that could be available for plants in limited irrigation will be increased by surfactant utilization and subsequently, IWUE for forage yield would be raised (Chaichi et al, 2015). The highest IWUE for grain yield have been reported in 50% ETc treatment (3.25 kg m -3 ) for corn by Di Paolo and Rinaldi (2008) which supports our findings.…”
Section: Water Use Efficiency (Wue) For Seed Yieldsupporting
confidence: 88%
See 3 more Smart Citations